Inflammation, physical activity, and chronic disease: An evolutionary perspective - Burini, Roberto Carlos [UNESP]; Anderson, Elizabeth; Durstine, J. Larry; Carson, James A. (Elsevier, 2020)
Low-grade inflammation is emerging as a common feature of contemporary metabolic, psychiatric, and neurodegenerative diseases. Both physical inactivity and abdominal adiposity are associated with persistent systemic low-grade inflammation. Thus, the behavioral, biological, and physiological changes that cause a predisposition to obesity and other co-morbidities could have epigenetic underpinnings in addition to various evolutionary scenarios. A key assumption involves the potential for a mismatch between the human genome molded over generations, and the issue of adapting to the modern high calorie diet and common built environments promoting inactivity. This biological mismatch appears to have dire health consequences. Therefore, the goal of this article is to provide a brief overview on the importance of inflammation as part of human survival and how physical activity (PA) and physical inactivity are critical regulators of systemic inflammation. The review will highlight anti-inflammatory effects of PA and exercise training from a metabolic and systemic signaling perspective, which includes skeletal muscle to utilization of fatty acids, TLR4 signaling, and myokine/adipokine effects. The available evidence suggests that PA, regular exercise, and weight loss offer both protection against and treatment for a wide variety of chronic diseases associated with low-grade inflammation through an improved inflammatory profile.
Keywords: Cytokines; Exercise; Immunity; Inflammation; Myokines; Obesity; Physical activity; Physical inactivity